Progesterone treatment enhances the expansion of placental immature myeloid cells in a mouse model of premature labor. (February 2019) - Gutzeit, Ola; Segal, Linoy; Hertz, Rivka; Burke, Yechiel; Paz, Gili; Hantisteanu, Shay; Ginsberg, Yuval; Hallak, Mordechai; Pencovich, Niv; Beloosesky, Ron; Weiner, Zeev; Fainaru, Ofer
Highlights: Progesterone treatment is known to attenuate preterm labor. Progesterone enhances the proliferation of immature myeloid cells (IMCs) in culture. Premature labor is accompanied by a decrease in IMCs in the mouse placenta. Progesterone pretreatment abrogates this effect. This effect might explain at least in part its role in prevention of preterm labor. Abstract: Introduction: immature-myeloid cells (IMCs) are proangiogenic bone marrow (BM)-derived cells that normally differentiate into inflammatory cells such as neutrophils, monocytes and dendritic cells (DCs). We characterized placental IMCs comparing their gene expression and subpopulations to tumor IMCs, and tested our hypothesis that progesterone that inhibits preterm labor, may affect their abundance and differentiation. Methods: differences between IMC-subpopulations in subcutaneous tumors versus placentas in C57BL/6 or ICR (CD-1) mice were analyzed by flow cytometry and gene expression was detected by microarrays. BM- and placental cells were incubated with or without progesterone and IMC subpopulations were analyzed. For preterm labor induction pregnant mice pretreated or not with progesterone were or were not treated with Lipopolysaccharide (LPS). Results: we detected enrichment of granulocytic-IMCs in placentas compared to tumors, paralleled by a decrease in monocytic-IMCs. mRNA expression of placenta- versus tumor IMCs revealed profound transcriptional alterations. Progesterone treated BM-CD11b + cells ex-vivo induced enrichment of granulocytic-IMCs and a decrease in monocytic-IMCs and DCs. LPS treatment in-vivo led to an increase in BM-IMCs in both progesterone pretreated or non-pretreated mice. In the placenta LPS decreased the IMC population while progesterone led to complete abrogation of this effect. Discussion: placental IMCs differ from tumor-IMCs in both subpopulations and gene expression. Progesterone enhances the proliferation of placenta-specific granulocytic IMCs ex-vivo and LPS induced labor is accompanied by a decrease in placental IMCs only in progesterone non-pretreated mice. We thus speculate that the protective effect of progesterone in preventing preterm labor may be explained at least in part by this specific anti-inflammatory effect.